A Study in Learning and its Patterns: A Field Study in the Baiji Refinery (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2024)
There are many advantages to learning styles. The most important of these is to think of them as tools for identifying individual differences. This helps us to help students learn and discover their teaching methods, providing them with communication tools to use in school subjects and many contexts, including outside school.Education is an essential process in life. It cannot be separated from human activity, but it is considered to be the essence of this activity. In the education process, people gain most of their personal experience, thereby growing and progressing and being able to face danger. Environmental. And be able to control, recognize, and utilize nature; express behavioral patterns in various forms; establish social institutions; create science, culture, and art; preserve and spread them from generation to generation; and teach them to become the energy that makes nature permanently change.